Correct citation and lectotypification of Quercus ×kabylica and Q. ×numidica (Fagaceae) - Coombes, Allen J.; Vázquez, Francisco María (Phytotaxa, 2021)
Publication details for the oaks Quercus ×kabylica and Q. ×numidica, described from Algeria, are determined, and lectotypes for both names, as well as for Quercus afares f. spinosa and Q. ×numidica var. brevisquama, are designated. Quercus ×kabylica and Q. ×numidica are regarded as representing the same taxon, for which the correct name is Q. ×numidica.